Macrina the Younger, Philosopher of God. By Anna M. Silvas - Hall, Stuart George (The journal of theological studies, 2008)
Anna M. Silvas has already distinguished herself as a translator and interpreter of the monastic life as received by brothers Basil the Great and Gregory of Nyssa. Now she turns her attention to their sister Macrina the Younger, the eldest of the family, and produces a thorough, soundly based analysis of the life and influence of the saint insofar as that is possible. She tells the tale of the retreat of Emmelia, widowed by the death of Basil the Elder, with her large family from Neocaesarea to Annisa. Her eldest daughter Macrina was betrothed at age 12 (not as young as Maraval says), and when her fiancé died committed herself to ascetic virginity.